Análise de jogos digitais infantis para o ensino e aprendizagem de História das Artes - Vieira, Izana Weber (2014)
Contemporary technologies favor the process of teaching and learning, construction of knowledge and awareness. In this proposal we are considering the diversity of media that today converge to a structured technological base through digital resources. Contribute to progress towards digital and social inclusion, in the areas of teaching and learning, production and distribution of knowledge. This research aims to contribute to the advancement of academic, educational, and social studies that take into account the interactive products and computer systems that allowed intense cultural exchange and reflection on specific themes: arts, sciences, games and new technologies. Providing significant findings in relation to the processes of teaching and learning and the production and distribution of knowledge on social networks and through identifying the possibilities of use of online interactive games as focused on the teaching of art history educational tools the child of 08 to 10. We draw dialogues with researchers such as Lev S. Vygotsky, Charles S. Peirce, Ana Mae Barbosa, Lucia Santaella and Hermes Renato Hildebrand, addressing issues related to the teaching and learning of children using games for educational development. As a result, the research proposes the analysis of educational games available on the internet and the modification of the game "face to face" that presents the possibility of generating educational content in visual arts, in addition to the development of a suitable prototype game "cara a cara" to through print and digital